Quest for a Theoretical Basis of Muslim-Christian Understanding - Tan, Samuel K. (Philippine Social Sciences Review; The Revolution of 1896 and the Continuing Struggle for National Dignity and Solidarity, Ed., Gil G. Gotiangco, 2010)
The search for a coherent theoretical basis of Muslim-Christian understanding is fundamental to the resolution of conflict that has remained a national concern. The emergence of various revolutionary groups in the Muslim South has reinforced the need for inquiry into the ideological roots of the movements. Three perceived paradigms have been articulated to explain the rationale of the Muslim-Christian struggle. The Marxist-Leninist paradigm tends to attribute the roots of Muslim-Christian conflict to colonialism and neocolonialism after 1946. The approach of "Political Islam" which contextually goes back to the 17th century rationale of Islamic movements in darul-islam tends to attribute the Muslim revolutionary struggle to the need to revitalize the Muslim community in the faze of challenges from modern changes introduced by Westernization. The dialogical alternative which has pined some adherents in the University of the Philippines seeks to de-emphasize religious differences and to promote mutual contact and desire for dialogue over common concerns and interests. The last approach offers a practical basis for bringing together parties in conflict and presents bright prospects for improving Muslim-Christian relations and understanding. But notwithstanding this optimistic perception, there remains some doubts that the dialogue movement can achieve declared goals because the unexpressed motivation of old, traditional Christian missions and evangelism still remains a pillar of Christian ideology tempered only by cultural accommodation and respect encouraged by Vatican II and liberal democracy.